The relationship between exercise intensity and energy contribution in short-duration intensive exercise - Shiraki, S.; Ogata, M.; Kigoshi, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
This study investigated the relationship between exercise intensity and energy contribution in shortduration intensive exercise. Two competitive university sprinters performed 30-s pedaling tests at four high intensity levels, following a submaximal test to determine the energy contribution during the 30-s pedaling tests by using the linear regression between exercise power and O2 demand. The energy contribution in each subject was almost constant during the 30-s pedaling tests at the four high intensity levels. Furthermore, O2 uptake and peak blood lactate concentration increased with increasing O2 demand in each subject. These results suggest that the energy contribution during short-duration intensive exercise at different high intensity levels is almost constant and that aerobic and anaerobic energy increase with increasing exercise intensity in each individual.